Influence of social media on the esthetic perception of the lip profile of orthodontic patients - Rebaque Pistoni, Tamara; de la Cruz Pérez, Javier; Nieto Sánchez, Iván (My University, 2023)
Objective: To identify the use of social media as an influencing factor of the orthodontic patient¿s preferences regarding the lip profile protrusion. Methods: A two-part cross-sectional questionnaire was distributed to orthodontic patients in Spain and The Netherlands. The first part collected general data and frequency of use of different social media. The second part consisted of a series of modified female and male silhouettes presenting different lip profile positions. Each participant was required to choose both the (male and female) most attractive silhouette and the least attractive one. Student t-test, one-way ANOVA and Chi-square test were performed. Effect sizes were calculated to express the magnitude of differences between samples. Results: The Spanish sample resulted in a moderate higher tendency (R2 = 0.060) to choose protrusive lips as the most attractive lip profile for females, on subjects with more frequent use of social media. A medium tendency (R2=0,26) was observed as result of low users of social media choosing and ideal lip profile for men. The Dutch sample showed that high users of social media tended to choose as attractive a more protrusive female lip profile versus low users (p < .01). This was also observed (p < .05) on male attractive lip profiles. Conclusions: Results suggest that frequent users of social media platforms tend to prefer more protruded lips than their less frequent counterparts. This information is valuable to be considered when formulating a treatment plan to satisfy the patient¿s expectations.